Impervious graphite and graphite heat exchanger
Patent Information
- Application Number
- CN202410722948.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-05
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-06-05
AI Technical Summary
[0004]本发明为解决现有的不透性石墨耐热、耐腐蚀性差,浸渍剂堵塞孔隙效果差,使不透性石墨的寿命较短的技术问题,提供一种不透性石墨,从分子设计的角度引入特殊结构提高新型生物基酚醛树脂(苯并噁嗪)的残碳率,并将其用作浸渍剂制备性能更好的不透性石墨
1.本发明不透性石墨孔隙填充效果好,不透性能更可靠,具有优异的耐酸碱、耐热、耐压等性能。
Smart Images

Figure CN118458761B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of non-metallic graphite heat exchanger preparation, specifically to an impermeable graphite and a graphite heat exchanger. Background Technology
[0002] Graphite is a material with low density, low heat capacity, and high thermal conductivity. Graphite has a certain degree of porosity, and impermeable graphite can be prepared by impregnation with an impregnating agent. Impermeable graphite possesses excellent heat resistance, thermal conductivity, and corrosion resistance, and has become an ideal material for various chemical equipment such as graphite heat exchangers. Currently, the most commonly used impregnating agent for graphite materials is phenolic resin. However, impermeable graphite impregnated with phenolic resin is difficult to adapt to alkaline media and suffers from drawbacks such as high viscosity and poor impregnation, greatly limiting its application. Other impregnating agents for graphite materials include small amounts of polytetrafluoroethylene (PTFE), furan resin, and water glass, but these are still unsuitable under conditions of strong alkalis and strong oxidizing acids. While PTFE has good corrosion resistance and excellent thermal stability, its poor bonding force with graphite micropores results in poor pore-closing effects, leading to a shorter lifespan for impermeable graphite.
[0003] Benzoxazine resin is a novel phenolic resin with a variety of unique properties. It features no release of small molecules during curing, low curing shrinkage, and flexible molecular design. Due to its flexible molecular design capabilities, diverse structures can be introduced into the molecule, thus endowing benzoxazine with unique properties to meet the requirements of various application fields. For example, introducing alkynyl groups or furan rings can increase its crosslinking density and improve heat resistance. Furthermore, benzoxazine resin exhibits excellent mechanical properties, heat resistance, and flame retardant properties. These unique advantages make it a promising replacement for traditional thermosetting resins such as ordinary phenolic resins, epoxy resins, and polyimide resins. Summary of the Invention
[0004] To address the technical problems of poor heat and corrosion resistance and poor pore-clogging effect of impregnating agents in existing impermeable graphite, resulting in a short lifespan, this invention provides an impermeable graphite by introducing a special structure from the perspective of molecular design to improve the residual carbon rate of a novel bio-based phenolic resin (benzoxazine) and using it as an impregnating agent to prepare impermeable graphite with better performance.
[0005] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: an impermeable graphite, wherein the graphite body is formed by sintering graphite powder, the graphite body has a porous structure, and the pores of the graphite body are filled with polybenzoxazine resin.
[0006] Furthermore, the graphite body is sintered from graphite powder with a particle size of 0.05~2mm; the pore size of the graphite body is 0.01~1μm.
[0007] Furthermore, the structural formula of the polybenzoxazine resin is as follows: .
[0008] The present invention also provides a method for preparing the above-mentioned impermeable graphite, comprising the following steps: (1) Place the sintered graphite body into the impregnation kettle; (2) The impregnation vessel is kept under vacuum, and the impregnation agent is drawn into the impregnation vessel and pressurized to 0.5~1MPa; (3) Dry the impregnated graphite body and put it into a heat treatment furnace for gradient temperature treatment to obtain the impermeable graphite. The thermosetting reaction equation is shown in equation (I): (I) The impregnating agent is a mixture of benzoxazine resin monomer and organic solvent, wherein the weight percentage of the benzoxazine resin monomer in the impregnating agent is 30-70%, and the structural formula of the benzoxazine resin monomer is: In the formula, n < 10000.
[0009] Furthermore, the gradient temperature treatment is as follows: 120℃ for 1~2h, 140℃ for 1~2h, 160℃ for 1~2h, 180℃ for 1~2h, 200℃ for 1~2h, 220℃ for 1~2h, and 240℃ for 1~2h.
[0010] Furthermore, the preparation method of the impregnating agent includes the following steps: 1) Cool furfurylamine in an ice-water bath, add 6 mol / L concentrated hydrochloric acid dropwise, then add formaldehyde solution dropwise, and raise the temperature to room temperature for 4-6 hours; add 6 mol / L NaOH aqueous solution for neutralization; then extract with chloroform, wash with water, dry with anhydrous Na2SO4, remove solvent by rotary evaporation, and vacuum dry at 55-80℃ to obtain DFDA; 2) Mix paraformaldehyde and solvent evenly; the solvent is toluene or a mixture of toluene and ethanol in a weight ratio of 2:1; 3) Mix DFDA, magnolol, and paraformaldehyde, heat to 70-90℃, and react until the liquid turns into a transparent wine-red solution, generating benzoxazine as the primary product; wherein the molar ratio of formaldehyde monomers of DFDA, magnolol, and paraformaldehyde is 1:1:4. The reaction equation is shown in (II): (II) 4) After separating the solvent, wash with alkali and water, and then vacuum dry at 60~90 ℃ to obtain benzoxazine resin monomer; 5) The impregnating agent is obtained by mixing the benzoxazine resin monomer with an organic solvent; the weight percentage of the benzoxazine resin monomer in the impregnating agent is greater than 50%.
[0011] Furthermore, in step 1) of the impregnation agent preparation, the mass ratio of furfuralamine, 6 mol / L concentrated hydrochloric acid, formaldehyde solution, and 6 mol / L NaOH aqueous solution is 60~110:125~190:20~38:250~380; the mass fraction of the formaldehyde solution is 37%.
[0012] Furthermore, the organic solvent in step 5) of the impregnation agent preparation is toluene, acetone, or chloroform.
[0013] In addition, the present invention also provides a graphite heat exchanger, including a shell and an impermeable graphite heat exchange unit, wherein the impermeable graphite heat exchange unit is made of the aforementioned impermeable graphite, and the impermeable graphite heat exchange unit is a perforated block of impermeable graphite, an impermeable graphite tube, or an impermeable graphite plate.
[0014] Furthermore, the surface of the impermeable graphite heat exchange unit is coated with a layer of polytetrafluoroethylene.
[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. The impermeable graphite of this invention has a good pore-filling effect, more reliable impermeability, and excellent resistance to acids and alkalis, heat, and pressure.
[0016] 2. The polybenzoxazine resin used in the impermeable graphite of this invention has the characteristics of no small molecule release during curing and low curing shrinkage, which ensures better bonding between polybenzoxazine and graphite micropores, enhances the pore-blocking effect, and extends the life of the impermeable graphite.
[0017] 3. The novel benzoxazine as an impregnating agent solves the problems of existing impregnating agents having large molecular weight, high viscosity, and difficulty in entering micropores. It can enter the pores of graphite very well and can reach a deeper pore depth; thus giving impermeable graphite better impermeability.
[0018] 4. The resin prepared by this invention, by introducing furan rings and allyl groups from a molecular design perspective, exhibits superior performance. This invention utilizes fully bio-based raw materials, is environmentally friendly, involves simple steps, allows for a variety of solvent choices, optimizes the preparation process, and is easily scalable for industrial production.
[0019] 5. Main-chain benzoxazides are more unique compared to mono- and difunctional benzoxazides. Furfurylamine-derived furan diamine (DFDA) can increase the crosslinking density of benzoxazides and improve their heat resistance. Magnolol extracted from plants is more environmentally friendly, and its allyl groups can further increase the crosslinking density. Synthesizing novel benzoxazides using these two raw materials can achieve better heat resistance while maintaining a simple and environmentally friendly process. Attached Figure Description
[0020] Figure 1The image shows the 1H NMR spectrum of the benzoxazine resin monomer prepared in Example 1 of this invention.
[0021] Figure 2 The infrared spectrum of the benzoxazine resin monomer prepared in Example 1 of this invention is shown.
[0022] Figure 3 The image shows the DSC curve of the benzoxazine resin monomer prepared in Example 1 of this invention.
[0023] Figure 4 This is a TGA curve of the polybenzoxazine resin of the present invention.
[0024] Figure 5 This is the MCC exothermic curve of the polybenzoxazine resin of the present invention. Detailed Implementation
[0025] The present invention will be further described below with reference to specific embodiments.
[0026] Example 1 A method for preparing impermeable graphite includes the following steps: Step 1: Mix paraformaldehyde and toluene / ethanol (2:1) mixed solvent, heat to 40°C, and stir for 1~1.5 h until there are no particles.
[0027] Step 2: Mix DFDA, magnolol, and paraformaldehyde in a molar ratio of 1:1:4. Add 30 ml of toluene / ethanol (2:1) mixed solvent for every 0.01 mol of DFDA. The reaction temperature is 70-90℃. The reaction time is 6-12 h until the liquid turns into a transparent wine-red solution, at which point the benzoxazine primary product is generated.
[0028] The preparation method of high-purity DFDA is as follows: 60-110g of furfurylamine is cooled in an ice-water bath, 125-190g of concentrated hydrochloric acid (6mol / L) is added dropwise, followed by 20-38g of formaldehyde solution. The mixture is heated to room temperature and reacted for 4-6 hours. Then, 250-380g of NaOH aqueous solution (6mol / L) is added dropwise for neutralization. The mixture is then extracted with 500ml of chloroform, washed 6-9 times with 300ml of water, dried with anhydrous Na2SO4, solvent is removed by rotary evaporation, and the mixture is vacuum dried in an oven at 55-80℃ for 6-10 hours to obtain high-purity DFDA.
[0029] Step 3: After separating the organic solvent, the product is obtained by alkali washing, water washing, and vacuum drying, which is the monomer of the novel benzoxazine resin (bio-based phenolic resin), with a yield of 84%. NMR and infrared characterization are as follows. Figure 1 , Figure 2 As shown. Figure 1The peak at 4.95 ppm represents the H atom in the O-CH2-N group of the oxazine ring; the peak at 4.05 ppm represents the hydrogen atom in the Ar-CH2-N group of the oxazine ring; the peaks at 3.35 ppm, 5.98 ppm, and 5.1 ppm represent the H atom on the allyl group; and the peaks at 6.11 ppm and 6.21 ppm represent the H atom on the furan ring. These peaks, along with the H atom peaks at 3.88 ppm and 4.1 ppm, collectively confirm the existence of the difuran ring structure. Figure 2 As shown in the figure, 911cm -1 The peak appearing at 798 cm⁻¹ is a characteristic peak of the allyl group. -1 and 1567cm -1 The peak at 1467 cm⁻¹ is caused by the binding of furan rings. -1 The peak at 933 cm⁻¹ represents the tetrasubstituted stretching vibration of the benzene ring. -1 1223cm -1 and 1364cm -1 The peak at that location is a characteristic peak of the oxazine ring.
[0030] Figure 3 This is a DSC curve of the benzoxazine resin monomer prepared in Example 1 of the present invention. The initial curing temperature (T) of the novel benzoxazine resin (bio-based phenolic resin) in the DSC curve is shown. onset ) and peak curing temperature (T peak The temperatures are 170℃ and 225℃, respectively.
[0031] Step 4: Mix the benzoxazine resin monomer with one of the organic solvents toluene, acetone, or chloroform to obtain the impregnating agent; the weight percentage of the benzoxazine resin monomer in the impregnating agent is 30%.
[0032] Step 5: Clean the sintered graphite body and dry it in a 70℃ drying oven for 4 hours. After cooling to room temperature, place the graphite body into an impregnation vessel, seal the impregnation vessel and evacuate it for at least 1 hour.
[0033] Step 6: Maintain a vacuum and draw benzoxazine resin (bio-based phenolic resin) impregnating agent into the impregnation reactor until it covers the graphite heat exchange unit by more than 3 cm. Close the impregnation liquid inlet, maintain for 30 minutes, then remove the vacuum and pressurize to 1 MPa, maintaining for 3 hours. Repeat this process 1-3 times. Release the impregnation liquid and dry in a 100℃ oven for 2 hours. Place in a heat treatment furnace for gradient high-temperature treatment to obtain an impermeable graphite heat exchange unit.
[0034] The gradient high-temperature treatment was as follows: 120℃ for 1.5h, 140℃ for 1.5h, 160℃ for 1.5h, 180℃ for 1.5h, 200℃ for 1.5h, 220℃ for 1.5h, and 240℃ for 1.5h.
[0035] Figure 4 This is the TGA curve of the polybenzoxazine resin of the present invention. The TGA curve shows that the resin's 5% mass loss temperature is 352°C, and the carbon yield (Y) at 800°C is... c The value is close to 63.5%. These two values are higher than those of most similar resins.
[0036] Figure 5 This is the MCC exothermic curve of the polybenzoxazine resin of the present invention. The graph shows that the resin reaches its maximum heat release rate (HRR) at 461°C. Its HRC value is 162 J / g. −1。 K −1 This indicates that the resin has excellent flame-retardant properties.
[0037] The air permeability and compressive strength of the impermeable graphite were tested.
[0038] Example 2 A method for preparing impermeable graphite differs from Example 1 in that toluene is used as the solvent in steps 1 and 2. The remaining steps are the same as in Example 1. Results show that the yield of the novel benzoxazine resin (bio-based phenolic resin) monomer is 70%, and the purity is similar to that of Example 1.
[0039] Example 3 A method for preparing impermeable graphite differs from Example 1 in that the benzoxazine resin monomer in step 4 accounts for 50% by weight. The remaining steps are the same as in Example 1.
[0040] Example 4 A method for preparing impermeable graphite differs from Example 1 in that the benzoxazine resin monomer in step 4 accounts for 70% by weight. The remaining steps are the same as in Example 1.
[0041] Impermeable graphite was prepared according to the methods of the above four embodiments, and its heat resistance, porosity, and weight gain of components before and after impregnation were tested. The results are as follows: Table 1. Detection results of Examples 1-4
[0042] The test data from the above embodiments show that the impermeable graphite prepared by this invention has excellent heat resistance (all above 263℃) and extremely low porosity (all below 1%). It can be used as a high-performance material in graphite equipment, thereby improving its operating conditions.
[0043] The test results of Examples 1 and 2 are similar, and the impregnation effects of the novel bio-based benzoxazine impregnating agents prepared with different solvents are not significantly different. This indicates that both solvents can be used to prepare high-purity novel bio-based benzoxazine resins, but the yields differ slightly in different solvents.
[0044] Comparing the test results of Examples 1 and 3 and 4, it can be found that as the weight ratio of benzoxazine resin monomer in the impregnating agent increases, the prepared impermeable graphite heat exchange unit has stronger heat resistance and lower porosity.
[0045] As can be seen from the above specific embodiments, the present invention is environmentally friendly and has a simple process. The above embodiments only describe the basic principles, main features, and advantages of the present invention. The present invention is not limited to the above embodiments, and further developments can be made without departing from the scope and innovation of the present invention. All such developments should be within the scope of the claims.
Claims
1. An impermeable graphite, characterized in that, The graphite body is formed by sintering graphite powder and has a porous structure. The pores of the graphite body are filled with polybenzoxazine resin. The graphite body is formed by sintering graphite powder with a particle size of 0.05~2mm. The pore size of the graphite body is 0.01~1μm. The structural formula of the polybenzoxazine resin is: .
2. The method for preparing impermeable graphite as described in claim 1, characterized in that, Includes the following steps: (1) Place the sintered graphite body into the impregnation kettle; (2) The impregnation vessel is kept under vacuum, and the impregnation agent is drawn into the impregnation vessel and pressurized to 0.5~1MPa; (3) Dry the impregnated graphite body and place it in a heat treatment furnace for gradient temperature treatment to obtain the impermeable graphite; the gradient temperature treatment is as follows: 120℃ for 1~2h, 140℃ for 1~2h, 160℃ for 1~2h, 180℃ for 1~2h, 200℃ for 1~2h, 220℃ for 1~2h, 240℃ for 1~2h. The impregnating agent is a mixture of benzoxazine resin monomer and organic solvent, wherein the weight percentage of the benzoxazine resin monomer in the impregnating agent is 30-70%, and the structural formula of the benzoxazine resin monomer is: In the formula, n < 10000; The preparation method of the impregnating agent includes the following steps: 1) Cool furfurylamine in an ice-water bath, add 6 mol / L concentrated hydrochloric acid dropwise, then add formaldehyde solution dropwise, and raise the temperature to room temperature for 4-6 hours; add 6 mol / L NaOH aqueous solution for neutralization; then extract with chloroform, wash with water, dry with anhydrous Na2SO4, remove solvent by rotary evaporation, and vacuum dry at 55-80℃ to obtain DFDA; 2) Mix paraformaldehyde and solvent evenly; the solvent is toluene or a mixture of toluene and ethanol in a weight ratio of 2:1; 3) Mix DFDA, magnolol, and paraformaldehyde, heat to 70-90℃, and react until the liquid turns into a transparent wine-red solution, generating benzoxazine as the primary product; wherein the molar ratio of formaldehyde monomers of DFDA, magnolol, and paraformaldehyde is 1:1:
4. 4) After separating the solvent, wash with alkali and water, and then vacuum dry at 60~90 ℃ to obtain benzoxazine resin monomer; 5) The impregnating agent is obtained by mixing the benzoxazine resin monomer with an organic solvent; the weight percentage of the benzoxazine resin monomer in the impregnating agent is greater than 50%.
3. The method for preparing impermeable graphite according to claim 2, characterized in that, In step 1) of the impregnation agent preparation, the mass ratio of furfuralamine, 6 mol / L concentrated hydrochloric acid, formaldehyde solution, and 6 mol / L NaOH aqueous solution is 60~110:125~190:20~38:250~380; the mass fraction of formaldehyde solution is 37%.
4. The method for preparing impermeable graphite according to claim 2, characterized in that, The organic solvent in step 5) of impregnation agent preparation is toluene, acetone or chloroform.
5. A graphite heat exchanger, characterized in that, It includes a shell and an impermeable graphite heat exchange unit, which is made of the impermeable graphite as described in claim 1, and the impermeable graphite heat exchange unit is a perforated block of impermeable graphite, an impermeable graphite tube, or an impermeable graphite plate.
6. A graphite heat exchanger according to claim 5, characterized in that, The surface of the impermeable graphite heat exchange unit is coated with a layer of polytetrafluoroethylene.
Citation Information
Patent Citations
Monocyclic benzoxazine intermediate with low viscosity and a plurality of functional groups and synthesis method thereof
CN101747288A
Polytetrafluoroethylene impregnant for manufacturing impermeable graphite and preparation method of polytetrafluoroethylene impregnant
CN116554415A
Full-biomass-based benzoxazine monomer as well as preparation method and application thereof
CN117551051A
Isostatic pressing flooding impermeable graphite piece
CN206266452U